Do-it-yourself (DIY) videos on maintenance of maize shelling machines: Northern Ghana, Gruni dialect with English subtitles - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
Short, vernacular do-it-yourself (DIY) videos by Africa RISING that smallholder farmers can refer to for tips on maintaining their mechanized maize shelling machines. Produced in the five major local dialects spoken in northern Ghana – Gruni, Dagbani, Dagare,Wale and Kasim; the videos will be played for communal viewing and compressed in size and distributed through social media applications such as WhatsApp, whose usage within communities in the region is on the rise.